Carbon nanotube electrodes for effective interfacing with retinal tissue - Shoval, Asaf; Adams, Christopher; David-Pur, Moshe; Shein, MArk; Hanein, Yael; Sernagor, Evelyne (Frontiers in Neuroengineering, 2009)
We have investigated the use of carbon nanotube coated microelectrodes as an interface material for retinal recording and stimulation applications. Test devices were micro-fabricated and consisted of 60, 30 μm diameter electrodes at spacing of 200 μm. These electrodes were coated via chemical vapor deposition of carbon nanotubes, resulting in conducting, three dimensional surfaces with a high interfacial area. These attributes are important both for the quality of the cell-surface coupling as well as for electro-chemical interfacing efficiency. The entire chip was packaged to fit a commercial multielectrode recording and stimulation system. Electrical recordings of spontaneous spikes from whole-mount neonatal mouse retinas were consistently obtained minutes after retinas were placed over the electrodes, exhibiting typical bursting and propagating waves. Most importantly, the signals obtained with carbon nanotube electrodes have exceptionally high signal to noise ratio, reaching values as high as 75. Moreover, spikes are marked by a conspicuous gradual increase in amplitude recorded over a period of minutes to hours, suggesting improvement in cell-electrode coupling. This phenomenon is not observed in conventional commercial electrodes. Electrical stimulation using carbon nanotube electrodes was also achieved. We attribute the superior performances of the carbon nanotube electrodes to their three dimensional nature and the strong neuro-carbon nanotube affinity. The results presented here show the great potential of carbon nanotube electrodes for retinal interfacing applications. Specifically, our results demonstrate a route to achieve a reduction of the electrode down to few micrometers in order to achieve high efficacy local stimulation needed in retinal prosthetic devices.